Prevalence of Risk Factors for Cardiovascular Diseases among Selected Military Personnel of Bangladesh - Rustom, ATMA; Rahman, Md Mahbubur; Iqbal, Syed Asif; Hasan, Mohammad Nazmul Amin (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Incidence of cardiovascular diseases (CVDs) in Bangladesh has been increasing as seen by various studies conducted across the country. Reliable data regarding modifiable risk factors of CVDs like body mass index (BMI), blood pressure (BP) and cholesterol levels are not available pertaining to military personnel. Objectives: To assess the prevalence of risk factors for CVDs among adult military personnel of a selected unit of the Bangladesh Army. Materials and Methods: This cross-sectional descriptive study was carried out among 835 adult participants from July 2018 to December 2018 in a military unit of Bangladesh Army. BP, BMI, fasting blood total cholesterol and sugar was assessed as per the standard procedure. Information regarding socio-demographic characteristics was collected using a pretested questionnaire. New American College of Cardiology guidelines-2017 used for categorization of hypertension and WHO criteria were used for grading obesity. Fasting blood sugar levels ≥ 126 mg/dl and total cholesterol> 200 mg/dl considered as increased. Results: Among the study population, 91% were non-smoker, 82% were married but stayed away from family and 85.3% were taking more fatty food. Only 6.2% of participants have given the history of taking extra salt. Prevalence of obesity raised serum cholesterol, and raised blood sugar were 0.4%, 0.6% and 0.6% respectively. Prevalence of pre-obese was 15.2% and stage-1 hypertensionwas 39.2%among 30-44 years’ age group. Conclusion: The high prevalence of stage-1 hypertension and its association with overweight in this young, physically active military population indicates an urgent need for targeted interventions to reduce the cardiovascular risk for a healthy life. Journal of Armed Forces Medical College Bangladesh Vol.14 (2) 2018: 186-189